1977
DOI: 10.1152/jappl.1977.42.6.909
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory responses during competitive marathon running

Abstract: To assess thermoregulatory responses occuring under actual marathon racing conditions, rectal (Tre) and five skin temperatures were measured in two runners approximately every 9 min of a competitive marathon run under cool conditions. Race times and total water losses were: runner 1 = 162.7 min, 3.02 kg; runner 2 = 164.6 min, 2.43 kg. Mean skin temperature was similar throughout the race in the two runners, although they exhibited a marked disparity in temperature at individual skin sites. Tre plateaued after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(51 citation statements)
references
References 0 publications
5
43
0
2
Order By: Relevance
“…The mechanisms for this increased severity of exertional versus classical heatstroke may relate to the presence of acidosis in exertional heat stroke or to any number of other factors associated with exercise-induced hyperthermia. The high rate of heat storage in the present study is comparable to the rate of heat storage observed in marathon runners finishing the race with total time of 150 min and final core temperature of approximately 41°C (Maron et al 1977). Thus, our volunteers had to deal with a rate of heat storage similar to that observed during a sports event, such as a marathon.…”
Section: Discussionsupporting
confidence: 73%
“…The mechanisms for this increased severity of exertional versus classical heatstroke may relate to the presence of acidosis in exertional heat stroke or to any number of other factors associated with exercise-induced hyperthermia. The high rate of heat storage in the present study is comparable to the rate of heat storage observed in marathon runners finishing the race with total time of 150 min and final core temperature of approximately 41°C (Maron et al 1977). Thus, our volunteers had to deal with a rate of heat storage similar to that observed during a sports event, such as a marathon.…”
Section: Discussionsupporting
confidence: 73%
“…Post-race rectal temperatures of 41.1°C have been observed in world-class athletes following races of 4.8 and 10 km (Robinson 1963) and in the winner of a 42-km race (Pugh et al 1967). To our knowledge, the highest observed T c in an asymptomatic runner was reported by Maron et al (1977), where T c was maintained between 41.6 and 41.9°C for the final 44 min of a 42-km road race. More recently, Byrne et al (2006) reported that 56% (n = 10) of their sample attained T c [ 40.0°C during a mass-participation 21-km road race in 27°C ambient temperature and 87% humidity, with two individuals attaining T c of 41.3 and 41.7°C.…”
Section: Introductionmentioning
confidence: 82%
“…That these observations arose from runners who successfully completed the exercise task, were champion athletes, or who ran faster than all other competitors despite T c [ 40°C, appears to refute the hypothesis that exhaustion occurs when a critical T c of *40°C is attained. A case-study observation that appears to refute the critical T c hypothesis was provided over 30 years ago by Maron et al (1977) who reported an end-spurt, displayed as a substantial increase in speed during the last mile of the race, in an individual with T c C 41.6°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged exercise has been shown to result in increases in body temperature which place high demands on the thermoregulatory system (Pugh et al 1967;Maron et al 1977). Due to the loss of sympathetic regulation in spinal cord injury, there is a reduced sweating capacity in the insensate skin (Randall et al 1966) and lack of vasomotor regulation below the level of the lesion (Hopman 1994).…”
Section: Introductionmentioning
confidence: 99%